THE EFFECT OF BRAND TRUST AND BRAND EXPERIENCE ON BRAND LOYALTY THROUGH EMOTIONAL BRAND ATTACHMENT TO WARDAH COSMETICS - Arti Mayangsari; Harti Harti (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of brand trust and brand experience on brand loyalty to Wardah cosmetics customers, which is mediated through emotional brand attachment. All female consumers of Wardah Cosmetics are the population in this study. By using the purposive sampling method, 100 (one hundred) respondents were selected. The sample of this research must consist of female consumers who have used Wardah Cosmetics for a minimum of 17 years and have usedWardah Cosmetics products at least 2 (two) times. The strategy applied to collect data is to use a questionnaire with a Google form. To evaluate the data, this study applies the